1976
DOI: 10.1515/znb-1976-0502
|View full text |Cite
|
Sign up to set email alerts
|

Oxotetrafluoro-vanadate(V): Die Kristallstruktur von [enH2] [VOF4(H2O)]2.

Abstract: Oxofluoro-vanadates(V), Crystal Structure, Vibrational SpectraThe crystal structure of [enH2][V0F4(H20)]2 has been determined from X-ray diffractometer data. Crystals are monoclinic, space group C2/c with Z = 4 in a unit cell of dimensions a = 16.576(13), 6 = 7.781(4), c = 10.338(8) Ä, ß= 120.0(1)°.The structure was refined by least-squares methods to R 0.053 for 1436 reflections. The structure contains monomeric [VOF4(H20)]~-ions with the oxygen atoms in trans position. The bond distances are 1.577 A (termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

1976
1976
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…Nevertheless, when the crystal structure of the salt was later determined, the anion was described as a polymeric ribbon of distorted [VOF 4 ] − octahedra connected through fluorine bridges . Further studies of MVOF 4 compounds with small cations (M = Na + , K + , Rb + , Cs + , Tl + , Ag + , NH 3 OH + ) also led to polymeric crystal structures with chains of [VOF 4 ] − anions connected through fluorine bridges. Studies with double protonated ethylene diamine (en) resulted in the structural characterization of [enH 2 ]­[VOF 4 ­(H 2 O)] 2 with a discrete anion in which vanadium is octahedrally coordinated due to a water molecule located trans to the oxygen atom in [VOF 4 ] − . The same octahedral coordination was reported for [C 4 N 2 ­H 12 ] 3 ­[V 2 O 2 F 8 ]­[VOF 4 ­(H 2 O)] 2 in which a discrete [VOF 4 ­(H 2 O)] − unit is highly distorted as a result of the trans -effect of the VO group on the lengthened V–OH 2 bond …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, when the crystal structure of the salt was later determined, the anion was described as a polymeric ribbon of distorted [VOF 4 ] − octahedra connected through fluorine bridges . Further studies of MVOF 4 compounds with small cations (M = Na + , K + , Rb + , Cs + , Tl + , Ag + , NH 3 OH + ) also led to polymeric crystal structures with chains of [VOF 4 ] − anions connected through fluorine bridges. Studies with double protonated ethylene diamine (en) resulted in the structural characterization of [enH 2 ]­[VOF 4 ­(H 2 O)] 2 with a discrete anion in which vanadium is octahedrally coordinated due to a water molecule located trans to the oxygen atom in [VOF 4 ] − . The same octahedral coordination was reported for [C 4 N 2 ­H 12 ] 3 ­[V 2 O 2 F 8 ]­[VOF 4 ­(H 2 O)] 2 in which a discrete [VOF 4 ­(H 2 O)] − unit is highly distorted as a result of the trans -effect of the VO group on the lengthened V–OH 2 bond …”
Section: Introductionmentioning
confidence: 99%
“…12,13 Moreover, a V 5+ analogue of the title compound, [C 2 N 2 H 10 ][VOF 4 (H 2 O)] 2 has also been reported to crystallise in a centrosymmetric space group. 14 It appears that inter-chain communication via H-bonding is essential to impose the net polar ordering, together with an appropriate number of cation-anion interactions. Hulliger 9 has suggested that any secondary, lateral interactions between such chains need only have an interaction energy of the order 3 kJ mol 21 or even less, in order to induce polar alignment of neighbouring chains.…”
mentioning
confidence: 99%
“…The V–O THF bond length is 2.40 Å in domain A and 2.46 Å in domain B, thus being considerably shorter than the respective sum of the van der Waals radii (3.92 Å) . The comparison of the V–O ligand distances in the [VOF 4 (THF)] − anion to the structurally related water containing [VOF 4 (H 2 O)] − anions , reveals that V–O THF (about 2.4 Å) is notably longer than V–O H 2 O (about 2.3 Å) most likely due to the larger size of the THF molecule. Fluorine atoms of the [VOF 4 (THF)] − anion are pushed toward the oxygen so that the O–V–F angles decrease in comparison to the starting [VOF 4 ] − anion (Table S4).…”
Section: Resultsmentioning
confidence: 95%
“…This is puzzling because compounds with acetonitrile coordinated with nitrogen atoms to the metal center are known for closely related [NbOCl 4 ] − and [NbOBr 4 ] − anions, ,, although crystal structures of [VOCl 4 ] 2– compounds show incorporated acetonitrile solvent molecules, similarly to our example, as not being coordinated to the metal center. , Moreover, electronic structure analysis shows that the vanadium atom is more positively charged in [VOF 4 ] − (+2.3) than in [VOCl 4 ] − (+1.9), and as such the former should be a better ligand acceptor . In contrast, crystal structures of [NbOF 4 ] − and [VOF 4 ] − , with water molecules coordinated to the metal center are known. A comparison of acetonitrile and water molecules as ligands in these coordination systems shows that water has, in addition to the electron-rich heteroatom capable of coordination, positively charged hydrogen atoms that can form hydrogen bonds with the anions, whereas no such positively charged hydrogen atoms are present in acetonitrile.…”
Section: Introductionmentioning
confidence: 99%